Income distribution in Uganda based on tax registers: What do top incomes say? - Markus Jäntti; Milly Isingoma Nalukwago; Ronald Waiswa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
We use income data from tax registers at the Uganda Revenue Authority from 2011 to 2017 to estimate top income inequality, focusing on the very top-the top 1, 0.1, and 0.01 per cent of the income distribution. The focus on the extreme top is facilitated by access to population data on formal sector income. The microdata from tax registries, submitted monthly to the Uganda Revenue Authority by employers, are supplemented by national accounts and population data that are used for control totals. Our results suggest that over the period we examine, incomes became substantially more heavily concentrated at the very top of the distribution.
Keywords: D3; N37; O15; 330; top incomes; inequality; tax register data